Teacher feedback and student learning–The students’ perspective - Leung, Albert; Fine, Peter D.; Blizard, Robert; Tonni, Ingrid; İlhan, Duygu; Louca, Chris (Elsevier, 2022)
Introduction: Feedback from teachers to students plays an important role in informing students about the outcome of their assessments. It contributes to students’ ongoing learning. The aim of this study was to investigate dental students’ perceptions of the feedback given to them by their teachers in Europe. Materials & methods: An online questionnaire was completed by dental students throughout Europe in this quantitative study. Data were collected via Google Forms, transferred to an excel spreadsheet and analysed using SPSS software Version 24. Results: 234 students studying in 9 different European countries completed the questionnaire. These students were born in 36 different countries within and beyond Europe. 84% (n = 197) were undergraduate students. 20.3% (n = 48) students reported receiving feedback following summative assessments. 81.2% (n = 190) students reported constructive criticism as their preferred mode of receiving feedback. 11.3% (n = 26) students did not know who delivered the feedback to them. 71% (n = 166) students felt that the feedback they received had a significant impact on their future learning. Conclusion: It would appear that there is some diversity in dental students’ perceptions of: i) who delivers feedback, ii) when feedback is given, iii) the consistency of feedback received, and iv) the style of feedback they preferred compared to that delivered by tutors. Feedback is being provided to dental students in an appropriate and helpful manner, although there is still room for improvement. Students were aware of the significance of feedback and its impact on future learning. Clinical significance: Most European dental students prefer to receive constructive feedback. Feedback was seen to have a significant impact on future learning despite over one in five students not knowing who had delivered their feedback. Feedback following clinical teaching should have a positive effect on students’ skills and motivation to learn.
Keywords: Feedback Delivery; Feedback Methods; Student Learning